2019
DOI: 10.1002/glia.23725
|View full text |Cite
|
Sign up to set email alerts
|

Properties of human astrocytes and NG2 glia

Abstract: Since animal models are inevitable for medical research, information on species differences in glial cell properties is critical for successful translational research. Here, we review current knowledge about morphological and functional properties of human astrocytes and NG2 glial cells and compare these data with those obtained for the comparable cells in rodents. Morphological analyses of astrocytes in the neocortex of rodents versus humans have demonstrated clear differences. In contrast, the functional pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 121 publications
(256 reference statements)
2
58
0
Order By: Relevance
“…On the other hand, previous immunohistochemical studies in human specimen suggested a similar NG2 expression pattern as in rodents. For example, NG2 could be detected in OPCs and pericytes in the healthy human CNS and was also found upregulated under pathological conditions [ 4 , 54 ]. Furthermore, NG2 was immuno-detectable in microglia/macrophages in samples from patients who encountered acute CNS injuries such as SCI or stroke, though the functions were not determined [ 7 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, previous immunohistochemical studies in human specimen suggested a similar NG2 expression pattern as in rodents. For example, NG2 could be detected in OPCs and pericytes in the healthy human CNS and was also found upregulated under pathological conditions [ 4 , 54 ]. Furthermore, NG2 was immuno-detectable in microglia/macrophages in samples from patients who encountered acute CNS injuries such as SCI or stroke, though the functions were not determined [ 7 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…A major criticism is that rodent neurons and astroglia might not be an appropriate model for human brain cells. 165 In particular, the high glycolytic metabolic activity with lactate production might be a characteristic of rodent cell cultures only. Recent technology utilizing inducedpluripotent stem cells (iPSCs) has enabled us to evaluate human neurons and astroglia in vitro.…”
Section: Metabolic Interaction Between Astroglia and Neuronsmentioning
confidence: 99%
“…Of note, most available evidence is based on in vitro studies using rodent neural cell cultures. A major criticism is that rodent neurons and astroglia might not be an appropriate model for human brain cells . In particular, the high glycolytic metabolic activity with lactate production might be a characteristic of rodent cell cultures only.…”
Section: Summary and Unsolved Issuesmentioning
confidence: 99%
“…Apart from astrocytes and oligodendrocytes, NG2 glial cells represent a third macroglial subtype in the CNS, which has received much attention in the past decade [for a detailed review, see ( 162 )]. In the literature, these cells are primarily referred to as OPCs, but also as complex cells, synantocytes, polydendrocytes, and GluR cells, as they depict glial and neuronal functions ( 163 , 164 ).…”
Section: Ng2 Gliamentioning
confidence: 99%